2004
DOI: 10.1093/alcalc/agh084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Morphine State-Dependent Learning in the Mouse: Involvement of Gabaergic, Opioidergic and Cholinergic Systems

Abstract: GABAergic, endogenous opioidergic and cholinergic systems are involved in the memory recall improvement by ethanol when it replaced morphine on the test day. A review of the literature suggests other possibilities such as the release of intermediate neurotransmitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Another important feature of pretraining morphineinduced amnesia in avoidance tasks is that it is abolished by pretesting administration of this drug (Izquierdo and Dias 1983;Bruins Slot and Colpaert 1999a;Khavandgar et al 2002Khavandgar et al , 2003Jafari et al 2004;Mohammad-Reza and Rezayof 2004;Vakili et al 2004). This phenomenon is called state dependence, i.e., the retrieval of learned information requires that the animal be in a state similar to that in which the memory for this information was acquired (Izquierdo et al 1981;Bruins Slot and Colpaert 1999a), and has been demonstrated after administration of several psychoactive drugs (Colpaert 1990;Jackson et al 1992;Bruins Slot et al 1999;Colpaert et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Another important feature of pretraining morphineinduced amnesia in avoidance tasks is that it is abolished by pretesting administration of this drug (Izquierdo and Dias 1983;Bruins Slot and Colpaert 1999a;Khavandgar et al 2002Khavandgar et al , 2003Jafari et al 2004;Mohammad-Reza and Rezayof 2004;Vakili et al 2004). This phenomenon is called state dependence, i.e., the retrieval of learned information requires that the animal be in a state similar to that in which the memory for this information was acquired (Izquierdo et al 1981;Bruins Slot and Colpaert 1999a), and has been demonstrated after administration of several psychoactive drugs (Colpaert 1990;Jackson et al 1992;Bruins Slot et al 1999;Colpaert et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs have been demonstrated, in our laboratory and by other investigators, to replace the pre-testing effect of morphine on the restoration of memory, e.g. adenosine [19] , nitric oxide [20] , ␣ -adrenoceptor drugs [21] , K ATP channel modulators [22] , glucose and insulin [23] and ethanol [24] .…”
Section: Discussionmentioning
confidence: 93%
“…Several other drugs have been demonstrated to improve memory impairment induced by pre-training morphine, when administered on the pre-test day, e.g. adenosine [21] , nitric oxide [22] , ␣ -adrenoceptor drugs [20] , K ATP channel modulators [23] , glucose and insulin [24] , ethanol [25] and histamine [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the first group of animals received saline (10 ml/kg) 30 min post-training and sulpiride (25,50 and 100 mg/ kg) 30 min before testing. The second group of animals received morphine (5 mg/kg, s.c.) 30 min post-training and sulpiride 45 min plus morphine 30 min before testing ( fig.…”
Section: Methodsmentioning
confidence: 99%